Documentary storytelling : creative nonfiction on screen - Bernard, Sheila Curran (Routledge, 2023)
"For nearly two decades, Documentary Storytelling has reached filmmakers and filmgoers worldwide with its unique focus on the key ingredient for success in the global documentary marketplace: storytelling. As this revised, updated fifth edition makes clear, nonfiction storytelling is not limited to character-driven journeys, but instead encompasses the diverse ways that today's top documentarians reach audiences with content that is creative, original, and often inspirational, all without sacrificing the integrity that gives documentary its power. The book is filled with practical advice for writers, producers, directors, editors, cinematographers, and others committed to reality-based filmmaking that seeks to reach audiences, raise awareness, address social issues, illuminate the human condition, and even entertain. In this new edition, Emmy Award-winning filmmaker and author Sheila Curran Bernard offers: a closer look at the way ethical nonfiction filmmakers take creative, authorial leaps while also remaining transparent with audiences; new tools for understanding how documentaries are structured, how they may rearrange time for storytelling effect, and how a simple narrative through-line can convey complexity without being a conventional "hero's journey"; new conversations with filmmakers and educators including Dawn Porter, Madison Burger, Tracy Heather Strain, June Cross, Heidi Gronauer, and Julie Casper Roth, and another look at conversations with Stanley Nelson and Orlando von Einsiedel. The book's website - available at www.documentarystorytelling.com - includes further interviews, related articles, and more"--